A Heuristic Approach Towards Drawings of Graphs With High Crossing Resolution. (29th November 2019) - Bekos, Michael A; Förster, Henry; Geckeler, Christian; Holländer, Lukas; Kaufmann, Michael; Spallek, Amadäus M; Splett, Jan
Abstract: The crossing resolution of a non-planar drawing of a graph is the value of the minimum angle formed by any pair of crossing edges. Recent experiments suggest that the larger the crossing resolution is, the easier it is to read and interpret a drawing of a graph. However, maximizing the crossing resolution turns out to be an NP-hard problem in general, and only heuristic algorithms are known that are mainly based on appropriately adjusting force-directed algorithms. In this paper, we propose a new heuristic algorithm for the crossing resolution maximization problem and we experimentally compare it against the known approaches from the literature. Our experimental evaluation indicates that the new heuristic produces drawings with better crossing resolution, but this comes at the cost of slightly higher edge-length ratio, especially when the input graph is large.